Hybrid command shaping and PD controller for sway suppression of rotary crane system -- Thesis [KIV] - WAN ABDULLAH, WAN NUR AAINA AYUNI (2016)
Crane systems were normally used for lifting, loading load from one point to others. The problem of crane systems is swing motion when payload is suddenly stopped after a fast motion. This project presents the development of input shaping with proportional derivative (PD) controller for sway suppression and trajectory tracking of rotary crane systems. The application of hybrid PD and input shaping technique can reduce the sway with better tracking responses. Firstly, PD controller is designed for angular position of rotary crane. Then, the input shaping is developed based on frequency response of PD control. The performance of the proposed controller is compared with PD-PID control scheme, in terms of time response specifications and sway reduction. The simulation results show that the PD-input shaping provide better control performance as compared to PD-PID scheme